Oseltamivir (Tamiflu(®)) in the environment, resistance development in influenza A viruses of dabbling ducks and the risk of transmission of an oseltamivir-resistant virus to humans – a review - Järhult, Josef D. (Co-Action Publishing, 2012)
The antiviral drug oseltamivir (Tamiflu(®)) is a cornerstone in influenza pandemic preparedness plans worldwide. However, resistance to the drug is a growing concern. The active metabolite oseltamivir carboxylate (OC) is not degraded in surface water or sewage treatment plants and has been detected in river water during seasonal influenza outbreaks. The natural influenza reservoir, dabbling ducks, can thus be exposed to OC in aquatic environments. Environmental-like levels of OC induce resistance development in influenza A/H1N1 virus in mallards. There is a risk of resistance accumulation in influenza viruses circulating among wild birds when oseltamivir is used extensively. By reassortment or direct transmission, oseltamivir resistance can be transmitted to humans potentially causing a resistant pandemic or human-adapted highly-pathogenic avian influenza virus. There is a need for more research on resistance development in the natural influenza reservoir and for a prudent use of antivirals.